Proximity to Oil Refineries and Risk of Cancer: A Population-Based Analysis. Issue 6 (7th October 2020) - Williams, Stephen B; Shan, Yong; Jazzar, Usama; Kerr, Preston S; Okereke, Ikenna; Klimberg, V Suzanne; Tyler, Douglas S; Putluri, Nagireddy; Lopez, David S; Prochaska, John D; Elferink, Cornelis; Baillargeon, Jacques G; et al.
Abstract: Background: The association between proximity to oil refineries and cancer rate is largely unknown. We sought to compare the rate of cancer (bladder, breast, colon, lung, lymphoma, and prostate) according to proximity to an oil refinery in Texas. Methods: A total of 6 302 265 persons aged 20 years or older resided within 30 miles of an oil refinery from 2010 to 2014. We used multilevel zero-inflated Poisson regression models to examine the association between proximity to an oil refinery and cancer rate. Results: We observed that proximity to an oil refinery was associated with a statistically significantly increased risk of incident cancer diagnosis across all cancer types. For example, persons residing within 0-10 (risk ratio [RR] = 1.13, 95% confidence interval [CI] = 1.07 to 1.19) and 11-20 (RR = 1.05, 95% CI = 1.00 to 1.11) miles were statistically significantly more likely to be diagnosed with lymphoma than individuals who lived within 21-30 miles of an oil refinery. We also observed differences in stage of cancer at diagnosis according to proximity to an oil refinery. Moreover, persons residing within 0-10 miles were more likely to be diagnosed with distant metastasis and/or systemic disease than people residing 21-30 miles from an oil refinery. The greatest risk of distant disease was observed in patients diagnosed with bladder cancer living within 0-10 vs 21-30 miles (RR = 1.30, 95% CI = 1.02 to 1.65), respectively. Conclusions: Proximity to an oil refinery was associated with an increased risk of multiple cancer types. We also observed statistically significantly increased risk of regional and distant/metastatic disease according to proximity to an oil refinery.